Effects of Green Manure and Clay on the Soil Characteristics, Growth and Yield of Peanut at the Coastal Sandy Soil - Muchtar Muchtar; Yoyo Soelaeman (UNIVERSITY OF LAMPUNG, 2010)
Effects of Green Manure and Clay on the Soil Characteristics, Growth and Yield of Peanut at the Coastal Sandy Soil (Muchtar and Y Soelaeman): Poor physical properties and limited amount of available nutrients were regarded as two main constraints possessed by coastal sandy soil for agricultural production. The objective of the study was to identify the effect of green manure and clay soil applications toward soils characteristic, growth and yield of peanut (Arachis hypogeae L.) in the coastal sand soil. A completely randomized design with factorial pattern 4 x 5 was applied in this experiment. The first factors were the rate of green manure application consisted of four levels, i.e. control, 5 Mg ha-1, 10 Mg ha-1 and 15 Mg ha-1 of green manures. The second factors were the addition of five different levels of clay, i.e. control, Vertisol, Alfisol, Inceptisol and Vertisol + Alfisol + Inceptisol. Each treatment combinations were replicated three times. Results of the study showed that the vertisol soil affecting physical characteristics of soil. The addition of Inceptisol soil affected chemical characteristic of soil, increased growth and yield of peanut. Application of 15 Mg ha-1 of green manures affected toward the characteristic of soils except of the crop yields. However, there was no significant interaction effect from both materials to all variables observed.